L’enseignement de la traduction japonais-français : une formation à l’analyse - Gile, Daniel (Meta, 1988)
SummaryMost Western translators of Japanese do not have quite a perfect understanding of the language. Some linguistic features of the Japanese language and its use by the Japanese also make it more difficult to translate than most other languages : its elliptic nature, its less than explicit logic, its grammar which provides few indications as to relations between nouns and noun clauses and few indications regarding time, its rapidly changing vocabulary and the rather loose way in which the Japanese tend to pose problems in translation . A third major problem for translators working from Japanese in the West is the lack of Japanese documentation and the difficulties encountered whenever they try to find Japanese resource persons to help them out with difficulties.Consequently, analysis is a must in translation from Japanese. Lexical analysis is mainly morphological in the case ofKango and phonological in the case of Gairaigo. Logical analysis of texts is necessary in testing meaning hypotheses, as the apparent "linguistic" meaning of text segments may be quite different from their true meaning. For complex, long or seemingly "agrammatical" or "illogical" sentences, the so-called "block analysis", which consists in identifying "blocks" encompassing noun phrases, identifying relationships between them, then streamlining sentences structurally and semantically until problems are pinpointed or solved, is an efficient analysis tool.